Impact of handgrip strength on cardiovascular, cancer and all-cause mortality in the Korean longitudinal study of ageing - Gyu Ri Kim; Jiyu Sun; Minkyung Han; Sohee Park; Chung Mo Nam (BMJ Open)
Objective To examine whether reduced handgrip strength, as a marker of muscle weakness, is linked with the risk of cardiovascular, cancer and all-cause mortality among older adults.Design We used data from the 2006 to 2014 Korean longitudinal study of ageing study. Estimates of handgrip strength were collected using a handheld dynamometer. Cox proportional hazard models with time-varying covariates were used to estimate HRs and their 95% CIs for all-cause mortality. The cause-specific hazards regression analysis was also used to model cardiovascular and cancer mortality, by treating deaths from the cause of interest as events and other causes of death as censored.Participants 5859 participants aged 50 years or older were followed up until death or until the date of censoring (31 December 2014).Primary outcome measures The study outcomes of interest were all-cause, cardiovascular and cancer mortality.Results Of the participants included in analyses, 515 individuals (8.8%) died, reflecting an overall crude mortality rate of 11.0 deaths per 1000 person-years. Participants in the lowest handgrip strength tertile showed an increased risk of all-cause and cardiovascular mortality evidenced by a multivariable adjusted HRs of 1.90 (95% CI 1.33 to 2.73) and 1.59 (95% Cl 1.08 to 2.34), respectively. However, there were no significant differences in the rates of cancer-related death, with HR of 1.29 (95% CI 0.92 to 1.81 [lowest vs highest tertile; p trend=0.21]).Conclusion These results demonstrate that lower handgrip strength is an independent predictor of mortality among a population-based sample of Korean elderly; highlighting the importance of interventions targeted at enhancing muscle strength for improvements in survival at older ages.